Towards understanding the biological foundations of perenniality. (January 2022) - Li, Zheng; Lathe, Rahul S.; Li, Jinping; He, Hong; Bhalerao, Rishikesh P.
Abstract : Perennial life cycles enable plants to have remarkably long lifespans, as exemplified by trees that can live for thousands of years. For this, they require sophisticated regulatory networks that sense environmental changes and initiate adaptive responses in their growth patterns. Recent research has gradually elucidated fundamental mechanisms underlying the perennial life cycle. Intriguingly, several conserved components of the floral transition pathway in annuals such as Arabidopsis thaliana also participate in these regulatory mechanisms underpinning perenniality. Here, we provide an overview of perennials' physiological features and summarise their recently discovered molecular foundations. We also highlight the importance of deepening our understanding of perenniality in the development of perennial grain crops, which are promising elements of future sustainable agriculture. Highlights: Perennial plants are a large category of flowering plants. Most have a polycarpic growth habit and some can reproduce vegetatively. Annuals' meristems largely behave in a straightforward and synchronised manner, becoming reproductive upon flower induction. Perennials' meristem activity is more complex, including an extended juvenile period, various forms of vegetative growth, and seasonally synchronised growth cycles. Emerging evidence indicates that components involved in floral transition have been coopted into regulatory mechanisms (e.g., transcriptional networks and key hormonal pathways) of perennials' developmental responses to environmental cues. Expanding knowledge of perenniality in grain perennials with agricultural potential may help to meet increasing food requirements while maintaining ecosystem security.